A systems approach to empowerment in manufacturing enterprises - McEwan, Anne Marie (Cranfield University, 1999)
Business challenges posed by turbulcnt local and global operating conditions are driving the adoption of new manufacturing strategies. Employee empowerment is vicwcd as a key enabler of these strategies within manufacturing enterprises. Analysis of the empowerment literature revealed that empowerment is poorly conccptualiscd. Little empirical evidcncc exists on the factors that influence the rcalisation of empowerment in manufacturing production. Paralld analysis in other domains reveals knowledge that could potcntially be applicd to opcrationalise empowerment in practice. This knowledge remains unexplored within the context of empowerment. The thesis proposition is that making empowerment operational depends on a prior understanding of the dimensions of the concept, which are specific to differing organisational contexts. The research endorses the necessity of considering empowerment from a differentiated systems perspective. Organisational control is confinned as a dominant management concern in operationali sing empowerment. It was determined that the development of a conceptual framework to synthesise the diffuse elements of empowerment could enhance understanding of the implications of operational ising the concept in manufacturing production. The author develops the framework using theoretical knowledge identified following a detailed analYsis of empowerment from literature. The theoretical propositions that constitute the conceptual framework are triangulated and the framework is operationalised using domain targeted industrial trials. The conceptual framework constitutes the prime deliverable of the research. The framework provides a mechanism for envisaging possible empowerment implementation scenarios within the context of manufacturing production. It is intended to be used by senior managers as a means of reflecting on the organisational contingencies of the application domain in which empowerment is to be operationalised.